How Perception use of e-Filling Technology Enhance Knowledge of Indonesian Disability Taxpayers and Impact Tax Compliance - Yana Hendayana; Harry Mulyadi; Fitriani Reyta; Radhi Abdul Halim (Budapest International Research and Critics University, 2021)
Taxes are a source of state revenue used to finance government spending and development. One of the taxes that the government imposes on its people is income tax including income from dissability. Referring to the large number of persons with disabilities in Indonesia, indeed there should be no difference in the treatment of the fulfillment of rights between normal people and disabilities. Philosophically and constitutionally, based on Pancasila and the 1945 Constitution, every citizen has a chance which is equally good in terms of work, accessing public facilities, get a decent life and livelihood, and so on. This is emphasized for the fulfillment of the rights of disabilities. Innovation of online accessibility for public services is one solution for disabilities taxpayers in Indonesia. SPT reporting via djponline one of them. The presence of efilling intended for makes disability taxpayers easier to participate in carrying out their tax obligations as citizens, but there is contrast in the field often taxpayers with special needs have not felt much benefit from the existence of this technology, for this reason the researcher decides to examine whether e-filling can affect the increase in taxpayer knowledge among disabilities, 85 samples taken from disabilities SMes in Bandung West Java, The data is processed using the partial least square method and using a quantitative approach, result shown as much as 58.47% the existence of e-Filling enchance the tax knowledge of persons with disabilities and non significance impact the tax compliance, they argue that all it needs is advanced technology on a disability-friendly website..